PENGARUH PEER COUNSELING BERBASIS MEDIA SOSIAL TERHADAP SIKAP REMAJA PUTRI MENGHADAPI PMS DI MAS AL WASHLIYAH 22 TEMBUNG PROVINSI SUMATERA UTARA TAHUN 2026 - Erin Padilla Siregar; Damayanty S Damayanty S; Diah Pitaloka; Fiska Surya Nesa; Faisal Faisal (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
Premenstrual Syndrome (PMS) is a cluster of physical, emotional, and behavioral symptoms frequently experienced by adolescent girls before menstruation, with prevalence in Indonesia estimated to reach 50-80%. Adolescent girls' attitudes toward managing PMS remain varied and largely suboptimal due to limited structured reproductive health education, including in religious-based schools. This study aims to determine the effect of social media-based peer counseling on adolescent girls' attitudes toward PMS at MAS Al Washliyah 22 Tembung, North Sumatra Province. The study used a quasi-experimental one group pretest-posttest design without a control group. The sample size was calculated using the Slovin formula and selected through simple random sampling. The research instrument was a Likert-scale attitude questionnaire that had been tested for validity and reliability. Data were analyzed using the Wilcoxon Signed Rank Test due to non-normal data distribution. Illustrative results show an increase in the proportion of the good attitude category from 20.0% to 65.0% after the intervention, with a p-value = 0.000 (p 0.05). These findings indicate that social media-based peer counseling has the potential to become an effective reproductive health education strategy relevant to the digital characteristics of today's adolescents.Keywords: peer counseling, social media, attitude, premenstrual syndrome, adolescent girls